Aktivitas Antibakteri Ekstrak Daun Angsana (Pterocarpus indicus) terhadap Staphylococcus aureus dan Salmonella typhimurium - Kun Mardiwati Rahayu; Syaharani Latifah (Jurnal Biologi dan Pembelajarannya (JB&P), 2026)
Bacterial infections caused by Staphylococcus aureus and Salmonella typhimurium remain a global health problem, particularly with increasing antibiotic resistance. This study aims to analyze the phytochemical profile and test the antibacterial activity of angsana (Pterocarpus indicus) leaf extract against these two bacteria. The study used an experimental method with a Completely Randomized Design (CRD) consisting of four extract concentrations (10%, 20%, 40%, and 80%), a positive control (chloramphenicol), and a negative control (DMSO), each with six replications. Antibacterial activity was tested using the Kirby-Bauer disc diffusion method, with the observation parameter being the diameter of the inhibition zone. The results showed that angsana leaf extract had concentration-dependent antibacterial activity against Staphylococcus aureus and Salmonella typhimurium, with the highest inhibition at 80% concentration of 19.69 mm and 19.24 mm, respectively (strong category). Comparatively, Salmonella typhimurium was more sensitive at medium concentrations, while Staphylococcus aureus showed a higher response at maximum concentrations. Although the extract's activity was still lower than chloramphenicol, these results demonstrate the potential of angsana leaf extract as a broad-spectrum antibacterial agent against both Gram-positive and Gram-negative bacteria. Therefore, angsana leaf extract has the potential to be developed as an alternative or complementary therapy in controlling bacterial infections, although further research is needed to optimize its effectiveness and further examine its mechanism of action.